2008
DOI: 10.1292/jvms.70.1289
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Sympathetic, Parasympathetic and Sensory Neurons Innervating the Distal Ileum of the Cattle

Abstract: ABSTRACT. After oral challenge of the pathological prion protein, the causative agent of bovine spongiform encephalopathy, the pathogen was first detected in the distal ileum and then deposited in the brain. The present study aims determining the possible neuronal transporting pathways from the ileum to the brain in the cattle using a tracer protein. After horseradish peroxidase was injected into the wall of the distal ileum in the calf, almost all labeled neurons were detected in the celiac and cranial mesent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…Our findings are consistent with the observations of Quinson et al (2001) in the rat, but differ slightly from data obtained by Luckensmeyer and Keast (1994), who did not find an innervation of the rat ileum from the CaudMG. Although few neurons of the SplanG and of the last TSC ganglia were involved in ICJ innervation, our results confirm observations in the rat by Luckensmeyer and Keast (1994) and in cattle by Ohmori et al (2008). Taken together, these data indicate that the sympathetic innervation of the gut is derived not only from postganglionic neurons located in abdominal PVG (Szurszewski and King, 1989) but also from TSC and SplanG.…”
Section: Origins Of the Sympathetic Innervationsupporting
confidence: 89%
See 1 more Smart Citation
“…Our findings are consistent with the observations of Quinson et al (2001) in the rat, but differ slightly from data obtained by Luckensmeyer and Keast (1994), who did not find an innervation of the rat ileum from the CaudMG. Although few neurons of the SplanG and of the last TSC ganglia were involved in ICJ innervation, our results confirm observations in the rat by Luckensmeyer and Keast (1994) and in cattle by Ohmori et al (2008). Taken together, these data indicate that the sympathetic innervation of the gut is derived not only from postganglionic neurons located in abdominal PVG (Szurszewski and King, 1989) but also from TSC and SplanG.…”
Section: Origins Of the Sympathetic Innervationsupporting
confidence: 89%
“…We believe that the paucity of FB-labeled DRG neurons could not be explained by an involvement of vagal sensory innervation of the ICJ, because vagal and DRG sensory fibers perform different functions (Cervero, 1994); furthermore, it has been shown that in the rat (Green and Dockray, 1987;Su et al, 1987), sheep (Chiocchetti et al, 2006), and cattle (Ohmori et al, 2008) only a minor or no (cattle) component of the afferent innervation of the ileum derives from neurons located in the distal vagal (nodose) ganglia.…”
Section: Spinal Afferent Neuronsmentioning
confidence: 98%